Complete sequence of mitochondrial DNA of Gloiopeltis furcata (Postels and Ruprecht) J. Agardh. Issue 2 (3rd July 2019) - Watanabe, Kei; Kishimoto, Takahiro; Kumagai, Yuya; Shimizu, Takeshi; Uji, Toshiki; Yasui, Hajime; Kishimura, Hideki
Abstract: Although most red algae produce agar and carrageenan, Gloiopeltis furcata produces funoran as polysaccharide component. In this study, the complete G. furcata mitochondrial genome was determined. It had a circular mapping molecular with the length of 25, 636 bp and contained 49 genes including 24 protein-coding, two rRNA, and 23 tRNA. Phylogenetic analysis showed that G . furcata was separated with the other polysaccharide-producing red algae. This is the first report of complete mitochondrial genome from funoran producing red algae.